2014
DOI: 10.1159/000363606
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus Open Partial Nephrectomy for Multilocular Cystic Renal Cell Carcinoma: A Direct Comparison Based on Single-Center Experience

Abstract: Objectives: To compare the treatment of laparoscopic (LPN) versus open partial nephrectomy (OPN) in patients with multilocular cystic renal cell carcinoma (MCRCC). Methods: Thirty-seven patients diagnosed with MCRCC were reviewed retrospectively between January 2007 and January 2013 at our institution. They were divided into two groups: group 1 (LPN) consisted of 19 patients (51.4%) and group 2 (OPN) of 18 patients (48.6%). RENAL and the Preoperative Aspects and Dimensions Used for an Anatomical classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The characteristics of the included studies are shown in Supplementary Table 1. All the included studies-6 prospective studies (23)(24)(25)(26)(27)(28) and 20 retrospective studies (22,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)-were cohort observational studies with no randomization. There were 3292 and 4803 patients in the LPN and OPN groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Supplementary Table 1. All the included studies-6 prospective studies (23)(24)(25)(26)(27)(28) and 20 retrospective studies (22,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)-were cohort observational studies with no randomization. There were 3292 and 4803 patients in the LPN and OPN groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, RLPN is characterised as minimally invasive, with a fast recovery time, but has high technical requirements for its operators. 17 One challenge of LPN is to shorten intraoperative WIT as much as possible, to ensure that postoperative residual kidneys maintain good renal function and to reduce the risk of postoperative acute and chronic renal failure. The consensus in the field is that a WIT of 25 minutes is the most appropriate inflection point for shortterm or long-term renal function damage.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms, clinical course and treatment regimen were registered. POPF were classified using the grading system established by the ISGPF [2] and by Clavien-Dindo grading for the classification of postoperative surgical complications [6,7]. A follow-up was done regarding fistula recurrence, malnutrition symptoms or abdominal/retroperitoneal reoperation.…”
Section: Methodsmentioning
confidence: 99%